Leeuwenhoek's Legatees and Beijerinck's Beneficiaries A History of Medical Virology in The Netherlands - van Doornum, Gerard (Amsterdam University Press, 2020)
The title of the book pays tribute to two Dutch scientists without whom virology would arguably not exist today, at least not in its present guise. The first is Antony van Leeuwenhoek, whose reports of microscopic discoveries in the early eighteenth century aroused interest in the world of invisible creatures. His findings laid the basis for a theory of a particulate cause of infectious diseases, but, as George Rosen wrote, without any tangible results in support of the theory (1993/1958, pp. 84-85). Some 250 years later Martinus Willem Beijerinck launched the discipline of virology with his idea that tobacco mosaic disease (TMD) was caused by a living contagious fluid or filterable living pathogen.